2010
DOI: 10.1593/neo.91422
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the Unfolded Protein Response Contributes toward the Antitumor Activity of Vorinostat

Abstract: Histone deacetylase (HDAC) inhibitors represent an emerging class of anticancer agents progressing through clinical trials. Although their primary target is thought to involve acetylation of core histones, several nonhistone substrates have been identified, including heat shock protein (HSP) 90, which may contribute towards their antitumor activity. Glucose-regulated protein 78 (GRP78) is a member of the HSP family of molecular chaperones and plays a central role in regulating the unfolded protein response (UP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
96
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(96 citation statements)
references
References 17 publications
0
96
0
Order By: Relevance
“…4, E and F). Interestingly, previous studies have reported that peptides covering Lys-585 in human HSPA5 (corresponding to Lys-586 in mouse HSPA5) are acetylated (24,25). Notably, trimethylation and acetylation give very similar changes in molecular mass, ϩ42.0106 Da, and ϩ42.0470 Da, respectively, and cannot be distinguished by lowresolution MS.…”
Section: Hspa-kmt Methylates Hsp70mentioning
confidence: 95%
“…4, E and F). Interestingly, previous studies have reported that peptides covering Lys-585 in human HSPA5 (corresponding to Lys-586 in mouse HSPA5) are acetylated (24,25). Notably, trimethylation and acetylation give very similar changes in molecular mass, ϩ42.0106 Da, and ϩ42.0470 Da, respectively, and cannot be distinguished by lowresolution MS.…”
Section: Hspa-kmt Methylates Hsp70mentioning
confidence: 95%
“…Upon ER stress, PERK, IRE1 and ATF6 are released from GRP78 and become activated. 51 A recent study indicates that SAHA induces acetylation of GRP78, leading to dissociation and activation of PERK, 52 providing a direct regulation of ER stress by HDAC inhibition.…”
Section: Atg5mentioning
confidence: 99%
“…In certain tumor cells, HDACs localized in ER affect the occurrence of ER stress [21-23]. In this study, we provided the first evidence that tunicamycin and bleomycin induced ER stress in alveolar epithelial cells via the upregulation of HDAC2/6, which mediate the formation of EMT.…”
Section: Discussionmentioning
confidence: 70%